Atomic-scale dynamics calculation of the formation of a flyer due to the shock wave induced by multi-pulse laser - Geng, Deshen (2021)
Laser-driven flyer technology is a new dynamic high-pressure loading approach for accelerating metal as a high-speed flyer. The flyer velocity can be effectively increased using a multi-pulse laser. However, the effect of interactions between the multi-pulse laser and the metal foil on flyer formation is not clear. Based on atomic-scale dynamics combined with the two-temperature model, this paper models for the first time the entire process of using a multi-pulse laser to form a high-speed flyer. It was found that the velocity, thickness, and integrity of the flyer are different for multi-pulse than for single pulse. For a fixed number of pulses, the velocity and integrity of the flyer can be increased by appropriately increasing the delay time. However, if the delay time is too long, the shock wave generated by the second pulse will cause the flyer to suffer from secondary shock loading, and the integrity of the flyer is destroyed. If the delay time between each laser beam is fixed, the energy of each beam and the resulting pressure of the shock wave can be reduced by increasing the number of pulses. In this case, the flyer does not undergo strong impact loading and the integrity of the flyer is improved. The shock wave caused by laser pulse can result in the crystal transformation from FCC to BCC or HCP, which enhances the formation of flyer. The results of this study are important for understanding the dynamic response of a metal subjected to a multi-pulse laser and for developing laser-driven flyer technology.